Topical Instillation of Resveratrol Preconditioned Wharton’s Jelly Mesenchymal Stem Cell Secretome Preserves Ocular Surface in Experimental Model of Severe Dry Eye Disease - Astaridewi, Diandra; Komaratih, Evelyn; Rindiastuti, Yuyun; Wirohadidjojo, Yohanes Widodo; Legowo, Djoko; Lestari, Ni Made Inten; Dewi, Diandra Astari; Satya, I. Made; Rantam, Fedik A.; Prakoeswa, Cita R. S. (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Secretome derived from Wharton’s jelly mesenchymal stem cells (WJ-MSC) has a beneficial effect for ocular surface regeneration; however, the high amount of vascular endothelial growth factor (VEGF) remains a challenge for its application. AIM: The aim of the study was to investigate the effect of resveratrol (RV) (VEGF reducing agent) preconditioned WJ-MSC secretome in Concanavalin A-induced severe dry eye model. METHODS: Pre- and post-experimental study composed of topical instillation of WJ-MSC secretome group, balanced salt solution control group, and normal control group. Tear production, tear break-up time (TBUT), corneal fluorescein dye staining, VEGF level in aqueous tear, goblet cell density, and inflammatory cells in the ocular surface were analyzed. RESULTS: Topical instillation of RV preconditioned WJ-MSC secretome successfully improved tear film production (p = 0.008) and TBUT (p = 0.008), promoted goblet cell restoration (p = 0.023) and reduced corneal fluorescein staining (p = 0.003), while inhibited infiltration of inflammatory cells (p = 0.01) and secretion of VEGF in aqueous tear (p = 0.003). CONCLUSION: Topical instillation of RV preconditioned WJ-MSC secretome has great potential as cell-free based therapy to preserve ocular surface in an experimental model of severe Dry eye disease.